Pemanfaatan Platform Digital sebagai Media Pemasaran Growol - Lukisworo, Agustinus Aryo (Jurnal Atma Inovasia, 2022)
Kuliah Kerja Nyata (KKN) Periode 79 of Universitas Atma Jaya Yogyakarta has been done from April to May 2021. On this period, the KKN was deployed on two Daerah Istimewa Yogyakarta regencies, Kulon Progo and Gunung Kidul. Kelompok 5 (Fifth group) of Unit A of this KKN, was assigned to Kalirejo Village, Kapanewon Kokap, Kulon Progo. Due to the Covid-19 pandemic, this period of KKN was carried out through online mode, without fieldwork and face-to-face interaction. Thus programs of this KKN was created upon secondary data which obtained by online investigations. Findings show that Kalirejo Village has a huge amount of potencies that fall into two categories, entrepreneurship, and socio cultural potency. Among that Kalirejo Village potencies, growol became an interesting potency to develop, particularly through a combination with digital platform utilization as a marketing medium for that traditional food. Hopefully, the digital marketing development will rise up the popularity and the demand of growol, dan lead to the Kalirejo Village economic development.